Luminescence chronology for the Paleolithic site of Xinmiaozhuang Locality 1 (XMZ1) in the Nihewan Basin, northern China, and its paleoenvironmental and archaeological implications. Issue 157 (August 2021) - Wang, Fagang; Guo, Yujie; Xian, Qi; Li, Manyue; Rui, Xue; Xie, Fei
Abstract: In contrast to the prevailing view that the Chinese Paleolithic has been dominated by the Mode 1 technology―with a slow and conservative development from the Early to the Late Pleistocene―recent discoveries indicate that the lithic technology might have developed into an 'advanced' phase in some parts of China, at least since the early Late Pleistocene. The Xinmiaozhuang Locality 1 (XMZ1), located on the southern edge of the Nihewan Basin in northern China, is one of the examples belonging to such an 'advanced' phase. Although the stone artifacts at this site still belong to the long-existing 'small-tool' industry (core-and-flake) in this basin, some 'advanced' traits, including discoidal cores, elongated flakes, and 'Mousterian-like' triangular points and scrapers, are present. We provide a dating of the XMZ1 using the multiple elevated temperatures (MET) post infrared (pIR) infrared stimulated luminescence (IRSL) procedure (MET-pIRIR) on both multigrained single aliquots and 'individual' grains of potassium-rich feldspars (K-feldspars). The consistency between the single-aliquot and single-grain K-feldspar equivalent dose results mutually confirmed the reliability of the obtained ages. Our chronology indicates that the cultural layer falls within the period of ca. 63–75 ka, corresponding to the early stage of the Marine Isotope Stage (MIS) 4. Based on the correlation of the cultural age to the environmental proxies of loess and stalagmites from China, we suggest that the site might have witnessed dramatic fluctuations of paleoclimate during the site formation. Additionally, based on the discoidal cores distribution, a potential corridor along the Xuefeng-Wu-Tainhang-Great Khingan Mountains for ancient humans migrating between South and North China is suggested. However, more archaeological and chronological studies are required to figure out the origin and the dispersal patterns of the discoidal core associated with lithic assemblage and the tool-makers in East Asia.